The Importance of Counseling Services in Islamic Schools - Fitri Br Surbakti; Olga Rizki Nadila; Yenti Arsini (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
In Indonesia, of course, there have been many religious-based schools, but the ones that are most often found are Islamic and Christian schools. In the growth of children until they reach their teenage years, taking education in religious schools is a good thing, besides they can still learn tolerance they will also learn more about their respective religions. However, no matter how good a religious school is, it certainly returns to the mental health of each child. There are children who cannot accept any situation and there are also children who can immediately accept the situation and polish themselves according to the environment they occupy. In this case, of course the school has a responsibility for the mentality of its students, schools must and must have guidance and counseling services for each child from any category, sometimes there are even students who experience mental damage but still attend normal schools. Especially in Islamic schools in Indonesia. in this study specifically will discuss how important it is to carry out guidance and counseling services in Islamic schools in Indonesia Abstrak Di Indonesia, tentunya sudah banyak berdiri sekolah-sekolah yang berbasis ke- Agamaan, tapi yang paling sering ditemukan ialah sekolah Islam maupun Kristen. Pada pertumbuhan anak hingga mereka menginjak usia remaja, menempuh Pendidikan disekolah keagamaan adalah baik adanya, selain mereka tetap bisa belajar toleransi mereka juga akan lebih mendalami mengenai agamanya masing- masing. Namun sebaik apapun sekolah keagamaan tentu kembali kepada mental health masing-masing anak. Ada anak yang tidak bisa menerima keadaan apapun dan ada pula anak yang bisa langsung menerima keadaan serta mempoles dirinya sendiri sesuai dengan lingkungan yang didudukinya. Dalam permasalahan ini tentu pihak sekolah memiliki tanggung jawab terhadap mentalitas para siswanya, sekolah harus dan wajib memiliki layanan bimbingan konseling terhadap masing-masing anak mulai dari kategori manapun, bahkan kadang kala ada siswa yang mengalami mental yang rusak namun tetap bersekolah disekolah normal. Terkhusnya disekolah Islam di Indonesia. Dalam kajian ini khusus akan membahas betapa pentingnya dilakukan layanan bimbingan konseling di Sekolah Islam yang ada di Indonesia. Katakunci: Konseling, Islam, Sekolah